How Can We Do Better? Experience of Hepatitis C Testing for Baby Boomers (1945–1965) in Six Primary Care Clinics. (4th October 2017) - Bluen, Benjamin; Kesaris, Anna; Coppock, Dagan; Boyle, Suzanne; Chou, Edgar; Lee, Dong Heun
Abstract: Background: Non-interferon based treatment regimens have transformed the therapeutic paradigm for hepatitis C infection. Universal one-time hepatitis C antibody testing is recommended by the Centers for Disease Control (CDC) for Americans born between 1945 and 1965 (the Baby Boomer "birth-cohort"). Limited data exists addressing testing strategies in primary care settings. This study aims to describe the experience of universal hepatitis C testing in the birth-cohort in six large primary care setting clinics. Methods: We performed a cross sectional study of universal hepatitis C testing in the birth-cohort in six primary care clinics from 2007 to 2016. Patients who were seen at least once in 2016 and had hepatitis C antibody testing were analyzed. We describe demographics, prevalence and duplicate testing rates. Results: Among 6615 patients seen, 4421 (69%) patients had hepatitis C antibody testing on six different primary care sites. Of those who had at least one hepatitis C test, 61.8% were male and 58.7% were African American. Of those tested 322 (7.2%) had a positive antibody result. One-third of patients (1452, 32.8%) had more than one hepatitis C antibody test. Duplicated testing was found to be more common in male than female patients (37.6% vs. 29.9%, P <0.001) and more common in White than Black or Asian patients (40.8% vs. 27.5%, 24.7%, P  < 0.001). Among those receiving duplicate testing, only 8 (0.5%) were newly diagnosed with infection. 58 (4%) patients had an unnecessary test as defined as the patient already having received a positive hepatitis C antibody result. Conclusion: We screened more than two-thirds of the birth-cohort for hepatitis C antibody at six primary care sites. High seroprevalence in the birth cohort validates current CDC recommendations for hepatitis C screening. However duplicate testing was not uncommon and, of those receiving duplicate testing, the serocoversion rate was low. This confirms one-time screening as an adequate strategy in the birth-cohort. With the availability of new and effective oral hepatitis C treatment regimens, one-time universal screening will be an important, economical component of linking hepatitis C patients with the care they need. Disclosures: E. Chou, Gilead: Grant Investigator, Research grant; D. H. Lee, Gilead: Grant Investigator, Research grant